Effects of COVID-19 Lockdown on Physical Activity, Sedentary Behavior, and Satisfaction with Life in Qatar: A Preliminary Study - Hermassi, Souhail; Sellami, Maha; Salman, Ahmad; Al-Mohannadi, Abdulla S.; Bouhafs, El Ghali; Hayes, Lawrence D.; Schwesig, René (International journal of environmental research and public health, 2021)
This study examined the effects of home confinement on physical activity (PA) and life satisfaction during the COVID-19 outbreak in Qatar. A total of 1144 subjects participated (male: n = 588; female: n = 556; age: 33.1 ± 11.1 years; mass: 76.1 ± 16.4 kg; height: 1.70 ± 0.11 m; body mass index (BMI): 26.1 ± 4.44  kg/m2). Online survey questions considered “before” and “during” confinement. Confinement reduced all PA intensities (ηp2 = 0.27–0.67, p < 0.001) and increased daily sitting time from 3.57 ± 1.47 to 6.32 ± 1.33 h per weekday (ηp2 = 0.67, p < 0.001). The largest reduction was detected for the sum parameter all physical activity (minutes per week, ηp2 = 0.67, p < 0.001; MET (metabolic equivalent of task)-minutes/week, ηp2 = 0.69, p < 0.001). Life satisfaction decreased, with the score for “I am satisfied with my life” (ηp2 = 0.76, p < 0.001) decreasing from 28.1 ± 4.81 to 14.2 ± 6.41 arbitrary units (AU). Concerning life satisfaction, the largest change was detected for the statement “the conditions of my life are excellent” (dmale = 7.93). For all parameters, time effects were indicative of large negative effects in both genders. In terms of magnitude, the difference between gender was greatest for the parameter “the conditions of my life are excellent” (difference between groups, d = 4.84). In conclusion, COVID-19 confinement decreased PA, increased sitting time, and decreased life satisfaction in Qatar. These precautionary findings explicate the risk of psychosocial impairment and the potential physical harm of reducing physical activity during early COVID-19 confinement in 2020.